Kontrol Sosial dan Framing Media Lokal dalam Polemik Pembangunan Masjid MIAH di Bogor - Suhaimi; Fauzan Kaifah; Cinta Rahmi (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2026)
Mass media perform a crucial social control function by monitoring public affairs and shaping public understanding of contentious social issues. Existing studies on religious conflict reporting in Indonesia primarily focus on national media framing, while limited attention has been paid to how local media construct religious legitimacy and social control in intra-Muslim conflicts. This study examines the coverage of the construction of the Imam Ahmad bin Hanbal (MIAH) Mosque in Bogor by two local media outlets, Metropolitan.id and Hariansinarbogor.com, using a qualitative approach based on Teun A. van Dijk's Critical Discourse Analysis at the levels of text, social cognition, and social context. The findings reveal that Metropolitan.id frames the controversy through narratives of social harmony and concerns over Salafi-Wahhabi influence, whereas Hariansinarbogor.com emphasizes constitutional rights, religious freedom, and the legality of mosque construction. These contrasting discourses demonstrate that local media do not merely disseminate information but actively construct competing narratives of religious legitimacy, reproduce symbolic power, and shape public perceptions of Islamic authority. This study contributes to the discourse on religious media framing by demonstrating that social control in local journalism operates through ideological discourse, making local media not only agents of public oversight but also producers of religious legitimacy and arenas for contesting Islamic authority in contemporary Indonesia.